309 Middle Fossa Approach to Lateralized Pontine Cavernomas in Children. (1st August 2016) - Calayag, Mark; Hoshide, Reid; Gonda, David D.; Meltzer, Hal S.; Fukushima, Takanori; Levy, Michael L.
Abstract: INTRODUCTION: Hemorrhagic cavernous malformations involving the lateral pontine region require complex surgical considerations to maximize complete resection of the cavernoma and associated hemorrhage while minimizing morbidity. We describe our experience through the middle fossa rhomboid approach in 8 children with cavernomas involving the pons, with lateralized hemorrhages extending through the pontine parenchyma. METHODS: Eight children underwent this approach over a 10-year period at Rady Children's Hospital of San Diego. There were 5 girls and 3 boys with a mean age of 13.2 years (±4.6 years). Six lesions were lateralized to the left and 2 to the right. An extended rhomboid approach was used in all patients. Landmarks were based on the Fukushima dual-fan model, which delineates this region by (1) the junction of the greater superficial petrosal nerve (GSPN) and V3; (2) the lateral edge of the porous trigeminus; (3) the intersection of the petrous ridge and arcuate eminence, and (4) the intersection of the GSPN, geniculate ganglion, and AE. Maximal bone removal was extended inferiorly beyond the inferior petrosal sinus to the clivus; posteriorly for unroofing the internal auditory canal; laterally for skeletonizing the geniculate ganglion, GSPN, and internal carotid artery; and anteriorly under the Gasserian ganglion. In all cases the lesions were approached posteromedially to the basilar artery at the junction of cranial nerve (CN) VI, superior to the anterior inferior cerebellar artery, and lateral to the trigeminal origin. Retraction of V3 allowed for our ability to avoid the region involving CNIV and the superior cerebellar artery. RESULTS: Seven cavernomas were completely resected, whereas a second peripheral lesion was not resected with the primary lesion in 1 patient. One patient had a transient CNVI palsy and 2 had transient trigeminal hypoesthesia/dysesthesia. One cerebrospinal fluid leak required oversewing of the wound. CONCLUSION: The middle fossa approach should be taken into consideration when an approach requiring minimal morbidity is needed to confront these complex lesions.